A cross-national perspective of migration and cancer: incidence of five major cancer types among resettlers from the former Soviet Union in Germany and ethnic Germans in Russia - Jaehn, Philipp; Kaucher, Simone; Pikalova, Lidia V.; Mazeina, Sofia; Kajüter, Hiltraud; Becher, Heiko; Valkov, Mikhail; Winkler, Volker (BMC cancer, 2019)
Few studies compared cancer incidence among migrants both to their host countries and to their population of origin. We aimed to compare cancer incidence of ethnic Germans who migrated from the former Soviet Union to Germany (resettlers) to those living in Russia as well as to the German and the Russian general populations.